Ischemic Heart Disease and Rheumatoid Arthritis—Two Conditions, the Same Background - Elena Rezuș; Luana Andreea Macovei; Alexandra Maria Burlui; Anca Cardoneanu; Ciprian Rezuș (Life, 2021)
Rheumatoid arthritis (RA) is one of the most frequent inflammatory rheumatic diseases, having a considerably increased prevalence of mortality and morbidity due to cardiovascular disease (CVD). RA patients have an augmented risk for ischemic and non-ischemic heart disease. Increased cardiovascular (CV) risk is related to disease activity and chronic inflammation. Traditional risk factors and RA-related characteristics participate in vascular involvement, inducing subclinical changes in coronary microcirculation. RA is considered an independent risk factor for coronary artery disease (CAD). Endothelial dysfunction is a precocious marker of atherosclerosis (ATS). Pro-inflammatory cytokines (such as TNFα, IL-1, and IL-6) play an important role in synovial inflammation and ATS progression. Therefore, targeting inflammation is essential to controlling RA and preventing CVD. Present guidelines emphasize the importance of disease control, but studies show that RA- treatment has a different influence on CV risk. Based on the excessive risk for CV events in RA, permanent evaluation of CVD in these patients is critical. CVD risk calculators, designed for the general population, do not use RA-related predictive determinants; also, new scores that take into account RA-derived factors have restricted validity, with none of them encompassing imaging modalities or specific biomarkers involved in RA activity.